The Dynamic Foundation: Harnessing Difference within the Matrix. (September 2019) - Kent, Jacinta
The world is awash with new technologies, increasing migration, and ever-expanding methods of communication—all of which are reflected in and around the groups we conduct. This article charts the evolution of Foulkes' group matrix before critically examining the notion of a foundation matrix in order to address the relevance of a concept that was created when the world seemed to move at a much slower pace. A development is offered that attempts to incorporate the dynamic and evolving world in which we live, harnessing difference within the matrix for transformational change.